2021
DOI: 10.3390/ijerph18010291
|View full text |Cite
|
Sign up to set email alerts
|

How and When Job Crafting Relates to Employee Creativity: The Important Roles of Work Engagement and Perceived Work Group Status Diversity

Abstract: Creative employees are treasured assets for organizations. However, relatively little is known about what specific actions employees can take to manage their own creative process. Taking a motivational perspective, this study examined how job crafting behaviors positively link to employee creative performance through work engagement, and whether perceived work group status diversity moderates this relationship. We conducted a weekly diary study in which 55 employees from a Chinese energy company were asked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Thus, rather than avoiding or withdrawing from hindering job demands, it focuses on actively addressing these demands by improving the work conditions or tasks. In contrast to decreasing hindering job demands, optimizing job demands related positively to work engagement (Constantini et al, 2021;Demerouti and Peeters, 2018;Tian et al, 2021).…”
Section: Job Crafting From An Individual Perspectivementioning
confidence: 98%
“…Thus, rather than avoiding or withdrawing from hindering job demands, it focuses on actively addressing these demands by improving the work conditions or tasks. In contrast to decreasing hindering job demands, optimizing job demands related positively to work engagement (Constantini et al, 2021;Demerouti and Peeters, 2018;Tian et al, 2021).…”
Section: Job Crafting From An Individual Perspectivementioning
confidence: 98%
“…For example, Liu et al (2021) demonstrated that employees’ perception of meaningful work could moderate the negative effect of perceived COVID-19 crisis strength on taking charge [ 52 ]. Tian et al (2021) found that work group status diversity could moderate the relationship between job crafting and employee creativity [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gel-denhuys et al 20 reported subscales of job crafting (eg, task, relational, and cognitive crafting) were related positively to work performance in a cross-sectional study. In addition, other longitudinal studies also have confirmed the positive association of job crafting with work performance 19,21–23 . Therefore, job crafting may be an influential intervention to increase work performance.…”
mentioning
confidence: 81%